2020
DOI: 10.3390/met10091163
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nakazima Test Suitable for Determining the Formability of Ultra-Thin Copper Sheets

Abstract: The objective is to propose an accurate method for determining the forming limit curves (FLC) for ultra-thin metal sheets which are complex to obtain with conventional techniques. Nakazima tests are carried out to generate the FLCs of a pure copper and a copper beryllium alloy with a thickness of 0.1 mm. Because of the very small thickness of the sheets, the standard devices and the know-how of this test are no longer valid. Consequently, new tools have been designed in order to limit friction effect. Two diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The specimens were divided into finite element meshes with an element size of h = 0.5 mm in the central region where failure was expected, and simulations were conducted using the Nakazima test model, with a constant punch velocity of 1 m/s. Based on the results, the authors concluded that comparing the numerical outcomes to the experimental FLC confirmed that it is feasible to utilize finite element simulations to determine FLCs Sreenath et.al, [13] The FLD (Forming Limit Diagram) for AA2014 and AA2024 was created using the Nakazima test simulation tool. The experimental results were then compared with the simulation results, and the simulation tool was validated.…”
mentioning
confidence: 88%
“…The specimens were divided into finite element meshes with an element size of h = 0.5 mm in the central region where failure was expected, and simulations were conducted using the Nakazima test model, with a constant punch velocity of 1 m/s. Based on the results, the authors concluded that comparing the numerical outcomes to the experimental FLC confirmed that it is feasible to utilize finite element simulations to determine FLCs Sreenath et.al, [13] The FLD (Forming Limit Diagram) for AA2014 and AA2024 was created using the Nakazima test simulation tool. The experimental results were then compared with the simulation results, and the simulation tool was validated.…”
mentioning
confidence: 88%
“…Formability is determined by the Nakajima method. 26 The Nakajima test must be performed to obtain the FLDs. To confirm the above response, copper sheets of two thicknesses (2 and 0.25 mm) for intermediate sheet strips were cut into the desired shape as per standard 17 as shown in Supplemental Figure 1(a)-(f) and Supplemental Table 3.…”
Section: Experimental Fld Confirmationmentioning
confidence: 99%
“…These tests involve a hemispherical punch to deform sheet metal blanks of various shapes until a fracture occurs [10]. The means growth using a circular die and hemispherical punch to create rectangular specimens of various sizes.…”
Section: Nakajima Testmentioning
confidence: 99%